Nuclear Aurora kinase A triggers programmed death‐ligand 1‐mediated immune suppression by activating MYC transcription in triple‐negative breast cancer. Issue 9 (12th July 2021) - Sun, Shulan; Zhou, Wei; Li, Xiaoxi; Peng, Fei; Yan, Min; Zhan, Yajing; An, Fan; Li, Xiaoyan; Liu, Yunyong; Liu, Quentin; Piao, Haozhe
Abstract: Background: Increasing studies have reported that oncogenes regulate components of the immune system, suggesting that this is a mechanism for tumorigenesis. Aurora kinase A (AURKA), a serine/threonine kinase, is involved in cell mitosis and is essential for tumor cell proliferation, metastasis, and drug resistance. However, the mechanism by which AURKA is involved in immune response regulation is unclear. Therefore, this study aimed to investigate the role of AURKA in immune regulation in triple‐negative breast cancer (TNBC). Methods: Peripheral blood mononuclear cells (PBMCs) were co‐cultured with TNBC cells. The xCELLigence Real‐Time Cell Analyzer‐MP system was used to detect the killing efficiency of immune cells on TNBC cells. The expression of immune effector molecules was tested by quantitative real‐time polymerase chain reaction (qRT‐PCR) to evaluate immune function. Furthermore, to validate AURKA‐regulated immune response in vivo, 4T1 murine breast cancer cell line with AURKA overexpression or downregulation was engrafted into BALB/c mice. The distribution and proportion of immune cells in tumors were further evaluated by immunohistochemistry and flow cytometry. Results: Downregulation of AURKA in TNBC cells increased immune response by activating CD8 + T cell proliferation and activity. Nuclear rather than cytoplasmic AURKA‐derived programmed death‐ligand 1 (PD‐L1) expression was independent of its kinase activity. Mechanistic investigations showed that nuclear AURKA increased PD‐L1 expression via an MYC‐dependent pathway. PD‐L1 overexpression mostly reversed AURKA silencing‐induced expression of immune effector molecules, including interleukin‐ (IL‐2), interferon‐γ (IFN‐γ), and perforin. Moreover, AURKA expression was negatively correlated with the enrichment and activity of tumor‐infiltrating CD8 + T cells in 4T1 engrafted BALB/c mouse model. Conclusions: Nuclear AURKA elevated PD‐L1 expression via an MYC‐dependent pathway and contributed to immune evasion in TNBC. Therapies targeting nuclear AURKA may restore immune responses against tumors. Abstract : The present study showed that nuclear AURKA rather than its kinase activity induced PD‐L1 expression via a MYC‐dependent pathway. In addition, downregulation of AURKA led to increased CD8 + T cell infiltration and activation in vivo. Thus, our data provided evidences for the involvement of AURKA in immune evasion of triple‐negative breast cancer.